SPATIAL ARRANGEMENT EFFECTS ON SOIL AND LEAF WATER STATUS OF WINTER WHEAT - J. Huang; Y. H. Chen; X. B. Zhou; P. Liu; J. J. Bi; Z. Ouyang (Journal of Animal and Plant Sciences, 2013)
The effects of row spacing (RS) on soil water content (SMC), leaf relative water content (RWC), leaf water potential (Ψ), and osmotic potential (π) in winter wheat were investigated in Northern China during 2006–2007 and 2007–2008. The experiments consisted of four planting patterns resulting in the same plant density (2.04 × 106 plant ha-1), with RS of 7, 14, 24.5, and 49 cm. A significant negative correlation was observed between RS and yield (Y) during both years (P < 0.05). RWC and π correlated positively with Y, and SMC while Ψ had an opposite effect on wheat. SMC decreased with increased RS, and RWC gradually decreased with the growth of crops. RWC and Ψ for RS 14, as well as π for RS 7 were higher than those for RS 24.5 and 49. At the flowering stage, the hourly Ψ of the different RS treatments produced a V-shaped curve trend in 1 day, and the coefficient of variation of RS 14 was relatively stable under different precipitation conditions. The results of this study indicated that the yield of RS 14 was significantly higher than that of RS 49 (P < 0.05), and an appropriate narrow RS was able to increase the yield of crops.
Keywords: Triticum aestivum; soil moisture content; leaf relative water content; leaf water potential; leaf osmotic potential; yield